Penentuan Nilai SPF (Sun Protection Factor) Ekstrak Metanol Buah Palem Merah (Crystotachys Renda Blume.) Sebagai Zat Aktif Tabir Surya - Syamsurizal, Syamsurizal; Wahyu, Delma Aziza; Maharini, Indri (Jurnal Pelayanan Kefarmasian dan Sains, 2025)
Background: Methanol extract from red palm fruit (Crystotachys renda Blume) contains secondary metabolites such as flavonoids, phenols, and tannins that have antioxidant properties. These compounds have the potential to act as sunscreen agents due to their ability to absorb UV-B radiation.Objective: This research aims to determine the Sun Protection Factor (SPF) value of methanol extract from red palm fruit as an active ingredient in sunscreen formulation. Method: This research began with the extraction process of red palm fruit simplicia using the maceration and reflux methods. The measurement of SPF values was conducted in vitro using UV-Vis Spectrophotometry at various concentrations, namely 100, 400, 600, 800, and 1000 ppm. Results: Based on the research findings, the methanol extract of red palm fruit has SPF values of 6.12; 24.43; 29.20; 30.67; and 31.00 at concentrations of 100, 400, 600, 800, and 1000 ppm, respectively. Conclusion: SPF testing shows that at a concentration of 1000 ppm, the methanol extract of red palm fruit has an SPF value of 31.00, which falls into the ultra protection category.